Pengaruh Terapi Reminiscence Terhadap Tingkat Kognitif Pada Lansia Di Wisma Lansia Taman Bodhi Asri - Evi Martina, Siska; Janno Sinaga; Rumondang Gultom; Anggi Lestari (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Impaired cognitive function is a deterioration of ability to remember and memory that can affect the elderly routine activities. Reminiscence is one method of expressing feelings that will trigger the emergence of self-confidence and feelings of respect of the elderly which has an impact on the emergence of positive coping that affects the perception and emotions of the elderly in facing a problem. The purpose of this study was to determine the effect of reminiscence therapy on cognitive level of the elderly at Wisma Lansia Taman Bodhi Asri. The type of research is quasy experiment with pretest-postest research design with control group design in which only the intervented group was given treatment. The population of this study were 65 elderly people. The sample of this study were 39 elderly people. The Sampling Technique used purposive sampling technique. The Data from the results of the study used the Paired sample T test. The results showed that the elderly who got intervene by reminiscence therapy group increased significantly (P value = 0.000). This shows that Ho was rejected, which means that there was an effect of reminiscence therapy on the cognitive level of the elderly at Wisma Lansia Taman Bodhi Asri. While there was no change in the control group used an independent t test with (P value = 0.753). This therapy was recommended as one of the therapies that can be done in an effort to maintain cognitive levels in the elderly.